Temperature and strain-rate dependence of the superelastic response in EBF3-fabricated and post-heat-treated NiTi shape memory alloy - Binqiang Li; Xianghong Liu; Tao He; Zhiping Li; Binbin Wang; J.P. Oliveira; Liang Wang; Jianxin Yu; Yanqing Su (Journal of Materials Research and Technology, 2024)
In the present work, the temperature and strain-rate dependence of the superelastic response behavior of NiTi shape memory alloys prepared via electron beam freeform fabrication (EBF3) technique and post-heat-treated is systematically studied. It is demonstrated that the response hysteresis of the EBF3-fabricated NiTi alloys during superelastic cycling decreases with increasing strain-rate at the same test temperature. However, the superelastic response of material gradually alters to a nearly linear mode with the increase of test temperature under the same strain-rate. The corresponding stable superelasticity recovery ratio decreases from 62.6 % to 47.6 % when the test temperature improves from 100 °C to 150 °C. This is mainly due to the activation of dislocations in the {011}<001> slip system of B2 austenite, in which they become plugged and entangled during plastic deformation, deteriorating the material superelastic recovery ability. These findings provide a selection basis for the service conditions of the rapidly prepared NiTi alloys under EBF3-fabrication and post-heat-treatment technology routes.